2022
DOI: 10.3390/agronomy12010113
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Study of the Redistribution of Some Bread Wheat Genotypes in Response to Climate Change in Egypt

Abstract: Climate change and global warming have become the most significant challenges to the agricultural production worldwide, especially in arid and semiarid areas. The main purpose of plant breeding programs now is to produce a genetically wide range of genotypes that can withstand the adverse effects of climate change. Moreover, farmers have to reallocate their cultivars due to their ability to tolerate unfavorable conditions. During this study, two field experiments and climate analysis based on 150 years of data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Accordingly, Krasnaja Zvezda should be used as a main parent in future crosses with other genotypes in drought tolerance improvement programs to produce cultivars having more tolerance to drought conditions, on one hand, and maintaining the genetic diversity among genotypes, on the other hand. Remarkably, some of the selected genotypes were previously reported as drought‐tolerant and high‐yielding genotypes (e.g., Misr‐1, Sids‐12, Sakha‐93, and Gimmeiza‐12) (Hamada et al., 2022), while the genotypes Beni Swief‐1, Beni Swief‐7, and Sohag‐5 were tolerant to tin (Sn) (A. Mourad et al., 2023). Additionally, A.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Krasnaja Zvezda should be used as a main parent in future crosses with other genotypes in drought tolerance improvement programs to produce cultivars having more tolerance to drought conditions, on one hand, and maintaining the genetic diversity among genotypes, on the other hand. Remarkably, some of the selected genotypes were previously reported as drought‐tolerant and high‐yielding genotypes (e.g., Misr‐1, Sids‐12, Sakha‐93, and Gimmeiza‐12) (Hamada et al., 2022), while the genotypes Beni Swief‐1, Beni Swief‐7, and Sohag‐5 were tolerant to tin (Sn) (A. Mourad et al., 2023). Additionally, A.…”
Section: Discussionmentioning
confidence: 99%
“…The highest value of grain yield of wheat was attained by the Shandaweel-1 cultivar compared to other cultivars (Elattar andMoustafa, 2021 andElmoselhy et al, 2022). Hamada et al (2022) pointed out that cultivars differ from each other in their ability to tolerate varied environmental conditions there by cultivating the appropriate cultivar in its best conditions to maximize its yield due to continual climate change as well redistribution of cultivars is one of the amendments that increase yield. Finally, the Shandawel-1 cultivar scored the highest yield of 5.22 ton ha -1 compared to other cultivars i.e., Giza-171, Misr-1, and Sakha-94 (Gad et al, 2020).…”
Section: Wheat Cultivars Performancementioning
confidence: 99%
“…Wheat is grown in widely varied climatic, and under both rain-fed and irrigated cultivation due to its high level of adaptation, hence, slightly dry, temperate climatic conditions are most suitable for wheat cultivation (Shalaby et al, 2020), to overcome water deficiency and save the irrigated area by means the development of high yield cultivars with stabilized performance under limited water environments (Shehab-Eldeen and Farhat, 2020). Hamada et al (2022) reported that the commercial wheat cultivars in the Egyptian agricultural system vary in their yield production, quality, and response to biotic and abiotic stresses thus should redistribute cultivars and cultivate them under appropriate conditions to obtain maximum productivity.…”
Section: Introductionmentioning
confidence: 99%
“…One of the oldest and most significant cereal crops in Egypt, wheat is regarded as the primary source of animal straw yield as well as the first food grain for all communities. But on a long term through the last decades the cultivated area suffered from high competition with the other winter crops, especially berseem clover (Hamada et al, 2022). Raising wheat productivity to meet the human need and declining the gap between local consumption and production could be approached, through several ways either horizontal or vertical, cultivate the newly reclaimed areas with high yielding, salinity and drought tolerant cultivars using precise irrigation systems and modern sowing methods, combining with proper cultural practices.…”
Section: Introductionmentioning
confidence: 99%
“…According to Hamada et al (2022), in order to achieve maximum productivity, commercial wheat cultivars in the Egyptian agricultural system should be redistributed and cultivated under suitable conditions because they differ in yield production, quality, and response to biotic and abiotic stresses.…”
Section: Introductionmentioning
confidence: 99%